The global health burden of pediatric chronic kidney disease: An analysis of the Global Burden of Disease database from 1990 to 2021 - Manan Raina; Raghav Shah; Jieji Hu; Bryce Pember; Thomas Cahill; Timothy Bunchman; Hui Kim Yap; Mignon McCulloch (PLoS ONE, 2025)
Background Chronic kidney disease (CKD) poses a significant global health challenge; however, its burden on pediatric populations remains underexplored. This study assesses the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of pediatric CKD attributable to type 1 diabetes mellitus, type 2 diabetes mellitus, hypertension, glomerulonephritis, and congenital anomalies of the kidney and urinary tract from 1990 to 2021. Methods Data were extracted from the Global Burden of Disease (GBD) 2021 database. CKD burden was stratified by etiology, age, sex, sociodemographic index (SDI), and geography. Average annual percentage changes (AAPCs) in incidence, prevalence, mortality, and DALYs were calculated. Results Globally, CKD-related mortality and DALYs decreased for type 1 diabetes mellitus (-2.176% AAPC), type 2 diabetes mellitus (-1.556%), glomerulonephritis (-0.854%), hypertension (-0.800%), and congenital anomalies of the kidney and urinary tract (-2.143%). The incidence of hypertension incidence increased (+1.299%). Boys experienced higher incidence and prevalence rates for all etiologies, while girls had more significant reductions in mortality and DALYs. High-SDI regions showed the steepest declines in CKD burden, while low-SDI regions experienced limited reductions and increasing hypertension prevalence. Conclusions Pediatric CKD burden reflects disparities by etiology, geography, and SDI. Interventions to improve early diagnosis, healthcare access, and targeted management strategies, particularly in low-SDI regions, are essential. Addressing obesity and improving treatment for glomerulonephritis are priorities. Standardized diagnostic criteria and broader global efforts are needed to mitigate the burden of pediatric CKD.